2003
DOI: 10.1103/physrevb.68.075301
|View full text |Cite
|
Sign up to set email alerts
|

Atom vacancy lines and surface patterning: The role of stress for Br-Si(100)-(2×1)at 700 K

Abstract: Using variable-temperature scanning tunneling microscopy, we studied Br-induced roughening of Si͑100͒-͑2 ϫ1͒ at 700 K. The roughening pathway requires Br-free dimers so that a saturated surface is inactive. Initial roughening involves the formation of atom vacancy lines and regrowth chains of Si dimers on the terraces. The atom vacancy lines grow longer through a stress-induced process that creates dimer vacancies. Br adatom repulsion then splits these dimer vacancies into pairs of single-atom vacancies. A ͑3ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The adsorbate concentration was determined directly from the STM images since Si dimers with Cl can be distinguished from bare dimers. 11,19 The samples were then heated to 700 K for extended imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorbate concentration was determined directly from the STM images since Si dimers with Cl can be distinguished from bare dimers. 11,19 The samples were then heated to 700 K for extended imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the processes and consequences of the production of pits and regrowth islands on Si(100)-(2ϫ1) have attracted extensive attention. [6][7][8][9][10][11][12][13] To date, however, there have been no studies of the step free energies on Si͑100͒ with halogen adatoms, though such investigations would provide insights into the effects of a large class of adsorbates.…”
Section: Introductionmentioning
confidence: 99%
“…Direct counting reveals that about 1 / 3 of the sites on the addimer chains are bare, while the Br atoms are almost conserved on the terrace. (The determination of halogen coverages has been discussed by Xu et al 6 ) For example, the four Si atoms in the lower right circle are all terminated with Br, while the six in the dashed ellipse are Br free. The structure near the center is made up of four dimers, and the contrast indicates that all of the Si adatoms are terminated with Br, except the two marked with arrows.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…The adlayers that grew from the ejected Si also have ͑3 ϫ 2͒ patches. Xu et al 6 followed this roughening in real time with variable temperature STM at 700 K, and they showed that ͑3 ϫ 2͒ first formed at high Br coverage but then reverted to ͑2 ϫ 1͒ as the concentration diminished; ͑3 ϫ 2͒ structures also form as a Si overlayer assembles in the presence of Br. In both cases, there is a reduction in total energy for ͑3 ϫ 2͒ rather than ͑2 ϫ 1͒ domains.…”
Section: Development Of "3 ã 2… Periodicity In the Si Adlayermentioning
confidence: 99%
See 1 more Smart Citation